The labor demand effects of refugee immigration: Evidence from a natural experiment - Paul Berbée; Herbert Brücker; Alfred Garloff; Katrin Sommerfeld (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
We study the labor demand effect of immigration on local labor markets by exploiting the fact that refugees in Germany are banned from working in the first few months after arrival. This natural experiment allows isolating a pure immigration-induced labor demand effect. For empirical identification we rely on the local presence of vacant military bases and on allocation quotas from a dispersal policy. The results are in line with our predictions from a theoretical framework with non-homothetic demand, where an increasing share in the consumption of necessities is associated with rising demand of labor-intensive goods: As the number of recently arrived refugees and thus the demand for locally produced goods increases, local employment increases particularly in non-tradable sectors in the short run. At the same time, unemployment drops while individual wages do not change significantly which can be traced back to widespread labor market rigidities in Germany. The isolation of labor demand effects complements the literature that isolates labor supply shocks from immigration, so as to gain a more comprehensive understanding of how immigration affects labor markets.
Keywords: J23; J60; H50; R10; 330; Labor demand; employment; immigration; refugees; natural experiment